2002
DOI: 10.1128/ec.1.4.606-612.2002
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with Btn2p Is Required for Localization of Rsg1p: Btn2p-Mediated Changes in Arginine Uptake in Saccharomyces cerevisiae

Abstract: Btn2p, a novel coiled-coil protein, is up-regulated in btn1⌬ yeast strains, and this up-regulation is thought to contribute to maintaining a stable vacuolar pH in btn1⌬ strains (D. A. Pearce, T. Ferea, S. A. Nosel, B. Das, and F. Sherman, Nat. Genet. 22:55-58, 1999). We now report that Btn2p interacts biochemically and functionally with Rsg1p, a down-regulator of the Can1p arginine and lysine permease. Rsg1p localizes to a distinct structure toward the cell periphery, and strains lacking Btn2p (btn2⌬ strains) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…We found that Btn2p was consistently concentrated in one or two dots close to the nucleus (17). Btn2p mediates late endosome-Golgi protein movements (49) and affects several proteins processed by this system (49)(50)(51). Nonetheless, the relation of the different activities of Btn2p remains unclear.…”
Section: Discussionmentioning
confidence: 86%
“…We found that Btn2p was consistently concentrated in one or two dots close to the nucleus (17). Btn2p mediates late endosome-Golgi protein movements (49) and affects several proteins processed by this system (49)(50)(51). Nonetheless, the relation of the different activities of Btn2p remains unclear.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have shown that Btn2 interacts with a wide variety of proteins (i.e., Rhb1, Yif1, and Ist2) (13,14,43) purportedly involved in numerous processes relevant to cell growth and homeostasis (i.e., ion, pH, or amino acid balance). However, the precise role of Btn2 in intracellular membrane transport has remained obscure.…”
Section: Discussionmentioning
confidence: 99%
“…5A), as previously shown (14,51). We examined Yif1 localization in a variety of cell types, including cells lacking BTN2 or RSG/RHB1, a small GTPase of unknown function (83) that was found to interact with Btn2, using the yeast two-hybrid screen (13). Interestingly, instead of the punctate labeling seen in wild-type cells, GFP-Yif1 was found to accumulate in the vacuole in both btn2⌬ and rhb1⌬ cells ( Fig.…”
Section: Fig 2 Btn2 Interacts Withmentioning
confidence: 99%
“…Galactose transport was measured by using techniques adapted from Chattopadhyay and Pearce (13). Each experiment was repeated independently 3-4 times to determine statistical significance.…”
Section: Methodsmentioning
confidence: 99%